Proceedings of the Seventh International Conference on Languages and Arts (ICLA 2018) 2019
DOI: 10.2991/icla-18.2019.113
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based Google Classroom In English Business Writing Class

Abstract: In this 4.0 era, digital technology and information system technology have integrated with teaching media and tool. From previous studies,Google Classroom is one of technologies whichhas been implemented inScience, Social Science, and Engineering Departments of Higher Institution. Based on PEOU and PU, the resultsare satisfying. Unfortunately, there weren't any studies that showwhether

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 6 publications
1
18
0
3
Order By: Relevance
“…The researcher found that all students increased their vocabulary quiz scores but limited their content knowledge. Apriyanti, et al (2018) [25] found that Google Classroom caused efficiency and effectiveness in the process of teaching and learning of English Business Writing class. Thus, the teacher's creativity is needed, and the role of a teacher to decide the use of technology in the class is big.…”
Section: Online Learningmentioning
confidence: 99%
“…The researcher found that all students increased their vocabulary quiz scores but limited their content knowledge. Apriyanti, et al (2018) [25] found that Google Classroom caused efficiency and effectiveness in the process of teaching and learning of English Business Writing class. Thus, the teacher's creativity is needed, and the role of a teacher to decide the use of technology in the class is big.…”
Section: Online Learningmentioning
confidence: 99%
“…Among others, the platform is deemed as cost effective (Inoue & Pengnate, 2018;Ventayen et al, 2018;Rajendram, 2019), where students for example only need to register for a Google account to start enrolling in a course through GC, without having to pay for any recurring subscription fee. In addition, GC is also quick and convenient to be used (Alim et al, 2019) as it offers easy and straightforward interface while providing a one-stop resource center for the students, which in turn helps educators to manage their classes more efficiently (Apriyanti et al, 2019;Sudarsana, et al, 2019). Moreover, GC provides flexibility to its users (Mafa, 2018), in which it is accessible anytime and anywhere through multiple forms of gadgets such as its own application in a smartphone or via its website in a personal computer with an internet access.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on the explanation above, it can be concluded that technology is an important part of education today. Online learning patterns that occur require students and teachers to learn and understand technology (Apriyanti et al, 2019). So, the role of technology can be an aid and other learning resources in the learning process (Unser, 2017).…”
Section: Introductionmentioning
confidence: 99%